The experience of pregnancy and motherhood in the career of Brazilian’s sportswomen: a qualitative study - Livia Gomes Viana-Meireles; Juliana Aparecida de Oliveira Camilo; Hiago Veras Gomes; Livian Valéria Oliveira da Silva; Eline Sousa Paz; Diego Cardoso Rodrigues; Domingo Palacios-Ceña (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Motherhood is a period there is a deconstruction of one identity and reconstruction of another, including changes in self-concept, commitment, and learning. For athletes who become mothers, these changes also occur and impact in their career. We aim to describe the experience of being pregnant for a group of Brazilian athletes, understanding the impact of maternity on the career and the postpartum for these women. A qualitative descriptive and exploratory study was conducted followed the guideline Standards for Reporting Qualitative Research (SRQR). We are using the semi-structured interviews with nine Brazilian athletes all of whom were professional athletes at the time they became pregnant. Maximum Variation Sampling and the snowball technique were used. The analysis was done using Iramuteq software, which performed Descending Hierarchical Classification (DHC) and Similarity Analysis. The nine athletes had a mean age of 38.3 years (SD: 5.5 years), from different levels and sports, and all had at least one child. We identified 488 text segments, which resulted in two branches, divided into five classes: History in sport (class 2); Pregnancy planning and immediate postpartum (class 5); reconciling the routines of athlete and mother (class 3); Social support narrative (class 4); Childcare (class 1). The findings indicate that athletes can have emotional ga ins in reconcile motherhood with their sports careers to the extent that they have social support, relative planning to become pregnant, and reconcile their athletic routine with baby care.